Tracked Changes. Sampling procedures for inspection by variables. Specification for single sampling plans indexed by acceptance quality limit (AQL) for lot-by-lot inspection for a single quality characteristic and a single AQL Part 1, (16th November 2022) - British Standards Institution,
No abstract available